Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Identification of hub genes and pathways associated with sevoflurane-induced synaptic loss in diabetic offspring via comprehensive transcriptome analysis - Xiaoru Sun; Xinke Guo; Tingmei Wu; Weimin Tao; Rong Lin; Yujie Song; Yuhan Zheng; Changsheng Ma; Fuyi Shen; Yilu Zhou; Zhendong Xu (Metabolic Brain Disease, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Distribution characteristic, synthesis mechanism and regulation measures of ethyl acetate in strong flavor Baijiu: A review - Jing Chen; Jing Zhang; Rong Zeng; Yang Lin; Yunxuan Duan; Chuan Song; Suyi Zhang; Yong Zuo (Food Bioscience, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Structural-taste relationship and molecular interaction mechanisms of umami peptides from Meretrix lyrata hydrolysates: Insights into key binding sites and thermodynamic drivers - Chunyong Song; Rong Jiang; Mingtang Tan; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Wenhong Cao (Food Bioscience, 2025)

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

A hybrid biomanipulation strategy to regulate seasonal dynamics of phytoplankton in a subtropical mesocosm experiment - Feng Wang; Wenyi Dong; Hongjie Wang; Xiaohui Sun; Helong Song; Zijun Dong; Zhiqiang Zuo; Botao Ni; Yanbing Ni; Chen Lin; Yiping Rong; Xi Lin (Science of The Total Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Integrative analysis of copper dysregulation and cuproptosis in postnatal hematopoiesis - Liyun Chen; Qian Wu; Chaohui Lin; Zijun Song; Yunxing Su; Chaodong Ge; Xue Wang; Hongbing Luo; Rong Wang; Yanfang Wang; Junxia Min; Fudi Wang (Science Bulletin, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)